COVID-19 Information Overload, Negative Emotions and Posttraumatic Stress Disorder: A Cross-Sectional Study - Wang, Jingjun; Huang, Xia; Wang, Ya; WANG, Mengmeng; XU, Jiajun; LI, Xiaolin (Frontiers in Psychiatry, 2022)
Background: Under the context of the COVID-2019 pandemic, a large amount of COVID-2019-related information can cause an individual’s perceived information overload, further halting the individual’s psychological health. As a minor psychological discomfort could develop severe mental disorders such as posttraumatic stress disorder, it is necessary to understand the chain linkage of COVID-19 information overload turn to posttraumatic stress disorder to ensure timely intervention can be offered at each point of mental state transformation. Hence, we examined the negative outcomes of COVID-2019 information overload and investigated the direct and indirect effects of COVID-2019 on posttraumatic stress disorder. Methods: A convenient sample of Chinese adults (n=1150) was investigated by an online survey from July 2020 to March 2021. The extent of COVID-2019 information overload was measured by the information overload severity scale on the text of the COVID-2019 pandemic. Psychological distress symptoms were measured using a 7-item anxiety scale (GAD-7), the 9-item Patient Health Questionnaire depression module (PHQ-9), and the psychometric properties of the PTSD Checklist (PCL-C). Structural equation modeling and bootstrap methods were utilized to analyze the relationships between variables. Results: COVID-19 information overload is positively related to an individual’s anxiety, depression, and posttraumatic stress disorder. Furthermore, COVID-19 information overload can indirectly affect an individual’s PTSD symptoms by increasing the feeling of depression. R2 values of anxiety, depression, and PTSD were 0.471, 0.324, and 0.795, respectively. Conclusion: COVID-19 information overload, anxiety, depression, and PTSD are negative psychological states, and each variable is closely linked with the others, suggesting the need for potential psychological interventions at specific times. Practical public training, such as crisis coping and information filtering, is essential. Regulation of technology companies is also essential.